UiO‐66 and hcp UiO‐66 Catalysts Synthesized from Ionic Liquids as Linker Precursors. Issue 2 (16th December 2020) - Ermer, Matthias; Mehler, Julian; Rosenberger, Björn; Fischer, Marcus; Schulz, Peter S.; Hartmann, Martin
Abstract: Using ionic liquids (ILs) as linker precursors, the well‐known metal‐organic framework (MOF) UiO‐66 (Universitetet i Oslo) and the recently reported MOF hcp UiO‐66 (hexagonal closed packed) have been successfully synthesized and characterized. The advantage of the applied novel synthesis approach is an economically and environmentally benign work‐up procedure, due to the better solubility of the IL. Additionally, the reactivity of the terephthalate anions is increased compared to terephthalic acid, resulting in faster MOF formation with an increased amount of defects in the MOF structure. In order to explore to the influence of defects on the catalytic performance, the cyclisation of citronellal to isopulegol was employed as test reaction. The activity of hcp UiO‐66 and fcc UiO‐66 (face centered cubic) is improved compared to other MOF or zeolite based catalysts, while the selectivity is similar. Abstract : The use of ionic liquids as linker precursor for the synthesis of the metal‐organic frameworks hcp and fcc UiO‐66 results in faster crystallization thereby reducing synthesis time and energy consumed. Furthermore, the catalytic activity of the MOFs in the cyclization of citronellal to isopulegol is increased due to defects within the frameworks while the selectivity is not affected.